Environment and development economics - Beijer Institute of Ecological Economics (Cambridge Cambridge University Press, 1996)
Access available online
Title from cover.
Keywords: Environmental economics -- Periodicals; Sustainable development -- Periodicals; Development economics -- Periodicals; Environmental policy -- Periodicals; Environmental economics -- Periodicals; Sustainable development -- Periodicals; Development economics -- Periodicals; Environmental policy -- Periodicals; Wirtschaftsentwicklung; Umweltschutz; Zeitschrift; Umweltökonomik.; Nachhaltige Entwicklung; Entwicklungstheorie; Theorie; Welt; ENVIRONMENTAL POLICY; ENVIRONMENTAL ECONOMICS; SUSTAINABLE DEVELOPMENT; ECONOMIC DEVELOPMENT; DEVELOPMENT